Alexandre Magno como homem-fronteira: virilidade e identidade greco-romana na construção do monarca macedônio de Plutarco e Arriano - Pause, Henrique Hamester (2021)
The objective of our research is to present some considerations about how the figure of Alexander the Great was perceived and reframed by the Roman writers Plutarch of Chaeroneia and Arrian of Nicomedia, during the 1st and 2nd centuries AD, focusing on the elements of gender/virility intersecting with the Greco-Roman cultural identity of the ruling elites. We will focus, especially, on the analysis of the works of these two authors that deal with the figure of Alexander, which are Book IV of Parallel Lives and On Fortune or Virtue by Alexander the Great, by Plutarch and The Anabasis of Alexander, by Arrian. We will seek, thus, to understand how the figure of Alexander, in these works, was described as an example by the authors to be studied in front of the Roman princes Trajan (98 - 117) and Hadrian (117 - 138), determining what they should or should not do when being a ruler in terms of virility and identity customs. We take the idea that Plutarch and Arrian have showed that everything Alexander achieved, his immense empire and his victories, he owed to his humanitas, acquired through education (παιδεία – paideia), moderation (gravitas/Σωφροσύνη – sôphrosýnê) and self-control (ἐγκράτεια – enkráteia).